1998
DOI: 10.1073/pnas.95.26.15458
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating multiple alternative hypotheses for the origin of Bilateria: An analysis of 18S rRNA molecular evidence

Abstract: Six alternative hypotheses for the phylogenetic origin of Bilateria are evaluated by using complete 18S rRNA gene sequences for 52 taxa. These data suggest that there is little support for three of these hypotheses. Bilateria is not likely to be the sister group of Radiata or Ctenophora, nor is it likely that Bilateria gave rise to Cnidaria or Ctenophora. Instead, these data reveal a close relationship between bilaterians, placozoans, and cnidarians. From this, several inferences can be drawn. Morphological fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
140
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(148 citation statements)
references
References 29 publications
(20 reference statements)
7
140
1
Order By: Relevance
“…Recent work has elucidated a broad repertoire of developmental regulatory genes in the Porifera, hinting at ancestral complexity in the early sponges (Leininger et al , 2014). While Placozoa has been considered sister to Bilateria (Collins, 1998), recent work suggests that the cnidarians are sister to Bilateria (e.g. Cannon et al , 2016).…”
Section: Developmental Comparisons and Phylogenetic Inferencementioning
confidence: 99%
“…Recent work has elucidated a broad repertoire of developmental regulatory genes in the Porifera, hinting at ancestral complexity in the early sponges (Leininger et al , 2014). While Placozoa has been considered sister to Bilateria (Collins, 1998), recent work suggests that the cnidarians are sister to Bilateria (e.g. Cannon et al , 2016).…”
Section: Developmental Comparisons and Phylogenetic Inferencementioning
confidence: 99%
“…Bridge et al, 1995). This may be unwise in light of evidence that bilaterians and cnidarians are relatively closely related (Collins, 1998;Kim et al, 1999). Because of the inclusion of a wider diversity of outgroups, this 66-taxon dataset is more appropriate to address hypotheses that deal with Hydrozoa as a whole, e.g., whether Hydrozoa is or is not monophyletic and what group is the sister clade of Hydrozoa.…”
Section: Accumulating Molecular Sequence Datamentioning
confidence: 99%
“…A study of the protein coding gene Hsp70 (Borchiellini et al 1998) indicated that Demospongiae form a clade with the Calcarea, excluding the Hexactinellida. However, recent gene sequence analyses supported a common Demospongiae-Hexactinellida taxon, whereas the Calcarea display closer affinities with the Ctenophora (comb jellies) than to Demospongiae (Cavalier Smith et al 1996;Van de Peer and De Wachter 1997;Collins 1998;Adams et al 1999;see also Zrzavy et al 1998).…”
Section: Introductionmentioning
confidence: 99%